The pricing of green bonds: external reviews and the shades of green - Gregor Dorfleitner; Sebastian Utz; Rongxin Zhang (Review of Managerial Science, 2021)
We investigate the asset pricing implications of the greenness of bonds. To estimate a green-pricing effect, we determine the 'green bond premium' as the difference between the yields of matched conventional and green-labeled bonds. On a cross-sectional average, green bonds experience a statistically significant positive premium. This premium increases with external greenness evaluations, i.e., investors accept premiums of up to 5 basis points for bonds with a substantial environmental agenda. This external validation effect, which is strongest for bonds that are rated dark-green, may offset not incurring information costs, as this effect decreases with increasing age of bonds.
Keywords: B76; B16; P20; 650; Green bond premium; External review; Second-party opinion; Shade of green; Climate finance; Impact investing